Invisibilisées et déconsidérées : autoreprésentations de personnes assistées sociales au Québec - Normand Landry; Anne Sophie Letellier; Lena A. Hübner; Anne-Marie Gagné; Marie-Josée Dupuis (Communiquer)
This article presents the results of an analysis of self-representations formulated by 105 welfare recipients. These representations are discussed in light of conceptual and theoretical tools from the field of cultural studies. By doing so, alternative narratives to those commonly used in public and media discourse emerge to name, define, and problematize the experiences of welfare recipients in Quebec. The results identify the reasons leading to social assistance, the difficulties experienced by welfare recipients, as well as the economic strategies that they deploy on a daily basis. They also highlight the ability for creative autonomous action among welfare recipients and their complex relationships with social assistance and poverty. These self-representations of welfare recipients are contextualized within the framework of social assistance programs in effect in Quebec and by quantitative data on the profiles of recipients of these benefits.